10.1016/S0271-7964(08)70191-5 (CrossRef Listing of Deleted DOIs, 2000)
OBJECTIVES: Laser lithotripsy efficiency is affected by the hydrodynamics of laser-induced vapor channels, which serve as conduits of laser energy to the target, but also contribute to stone retropulsion and limit clinical outcomes. The objective of this study is to develop a theoretical model describing the evolution of a vapor bubble near a solid boundary, its transformation into a vapor channel, and its subsequent oscillatory behavior during long-pulsed laser irradiation in aqueous media. METHODS: A simplified physical model was constructed in which laser radiation generates a vapor bubble near a rigid wall. The liquid phase is described using potential flow theory, while the vapor is treated as a gas in equilibrium. The governing equations are solved using a finite element method with a moving boundary mesh to track bubble and channel evolution. To validate the model predictions, experimental data were collected using high-speed imaging and transmission measurements. RESULTS: Numerical simulations reproduced the formation of an oscillating vapor channel and its dependence on the fiber-wall gap. The predicted oscillation frequency and duty cycle showed good agreement with experiments, particularly for gaps of 200-500 μm. Analysis of the flow field and wall forces indicates that liquid inertia is the primary driver of vapor channel oscillations and associated momentum transfer to the wall. CONCLUSION: The model provides quantitative insight into the mechanisms governing vapor channel oscillations during long-pulsed laser irradiation. The framework serves as a basis for developing a computationally effective predictive model of retropulsion, which is necessary for the rational design of laser pulse strategies aimed at reducing retropulsion in laser lithotripsy.